Hasil Belajar Kognitif Peserta Didik Kelas X Pada Materi Biosfer Dengan Menggunakan Media Permainan Ludosfer Di Sman 17 Jakarta - Pramesti, Iftah Luthfiana; Hardi, Ode Sofyan; Setiawan, Cahyadi (Peneliti.net, 2024)
This study aims to determine the effect of using Ludo Geography learning media on cognitive learning outcomes of students in class X biosphere material at SMAN 17 Jakarta. This study used the Quasi Experimental Nonequivalent Control Group Design method on the basis of considering the criteria that research is to look for the effect of certain treatments under controlled conditions and to find out whether there are effects of treatment on the subjects investigated with the aim of comparing one or more experimental groups that are given treatment with one comparison group that is not given treatment. The sampling technique in this study used simple random sampling. The samples used in this study were class X-G as the experimental class which was given treatment using the learning media game Ludo Geography of the Biosphere (LUDOSFER) and class X-F as the control class which was given treatment using PowerPoint media. Comparison of cognitive learning outcomes of students in the experimental class with an average pre-test of 61.32 and a post-test of 84.71 which is significantly higher than the average pre-test of 58.97 and a post-test of 80.29 in the control class. Data analysis using the average two equation of hypothesis test (Independent Sample T-Test) obtained that the significance level (Sig.) was (0.000 <0.05), then H0 was rejected and Ha was accepted, so that there was a positive effect on increasing student learning outcomes in class X SMAN 17 Jakarta after using LUDOSFER game media in the geography learning process.